The Use of Raktepel Media (Rainbow Egg Rack) to Improve Mathematical Concept Understanding of Grade II MI Students - Arifin, Fatkhul; Muzdalifah, Dinda (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
The utilization of teaching media is still very limited. Especially for teaching math concepts in madrasah ibtidaiyah. This study aims to explain the effect of using Raktepel (Rainbow Egg Rack) media on students' understanding of mathematical concepts on multiplication and division material in class II MI Nurul Islamiyah Kedaung. The research method used is a quasiexperiment with a Posttest-Only Group Design research design. The sample in this study consisted of an experimental class of 23 students and a control class of 23 students. The results showed that students who were taught using Raktepel media obtained a higher average score than the average score of the mathematical concept understanding ability of students who were taught without using Raktepel media. This can be seen from the results of the t-test of the post-test of the experimental class and the control class of 0.007 with a significance level of 0.05. So, it can be concluded that this Raktepel media has a significant effect on helping grade II students at MI Nurul Islamiyah Kedaung to understand the concepts of multiplication and division.